2018
DOI: 10.3390/ijerph15122832
|View full text |Cite
|
Sign up to set email alerts
|

Response of Ruderal Species Diversity to an Urban Environment: Implications for Conservation and Management

Abstract: Anthropogenic activities have weakened the invasion of ruderals and increased the number of non-native species in urban areas. Ruderals are an important component of urban plant diversity and are of great significance to the sustainable development of urban green space. We used the tessellation–randomized plot method to examine the composition and biodiversity of ruderal species among urban land use types (LUTs) in the built-up areas of Beijing. Soil samples from the surface to a depth of 10 cm were taken from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 32 publications
1
9
0
2
Order By: Relevance
“…The increase of ruderal species in the parks located along the Shonai River suggested that colonization of ruderal species depended more on the massive artificial disturbances in a megacity. Consistent with our study, many studies have reported that a large number of ruderal plants are always recognized in urban areas with stronger anthropogenic pressure [37,38]. Interestingly, the semi-natural habitats showed opposite trends to the artificial habitats.…”
Section: Plant Species Richness In Artificial and Semi-natural Habitatssupporting
confidence: 90%
See 1 more Smart Citation
“…The increase of ruderal species in the parks located along the Shonai River suggested that colonization of ruderal species depended more on the massive artificial disturbances in a megacity. Consistent with our study, many studies have reported that a large number of ruderal plants are always recognized in urban areas with stronger anthropogenic pressure [37,38]. Interestingly, the semi-natural habitats showed opposite trends to the artificial habitats.…”
Section: Plant Species Richness In Artificial and Semi-natural Habitatssupporting
confidence: 90%
“…Although the distance to the city center was included in the GLM model, the effect was stronger in the semi-natural habitat. This negative relationship has been aptly explained by the increased habitat diversity and human disturbance at the urban centers [37,38]. Hence, a short distance to the city increases the possibility of the propagation of ruderal plants.…”
Section: Driving Factors Affecting Different Types Of Vegetationmentioning
confidence: 99%
“…Such plant communities are recommended to be used with their natural structure or with a slightly corrected species composition. Some researchers consider spontaneous vegetation as an important component of urban green space diversity, which is essential for the sustainable development of urban ecosystems (Del Tredici, 2014;Guo et al, 2018). The dominance of alien species in urban landscaping, in their opinion, decreases the functional stability of such ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Em determinadas circunstâncias, essas plantas são as únicas encontradas nesses ambientes, sendo, as responsáveis pela proteção do solo contra a erosão provocada pela chuva e pelo vento (SOUZA;PALEARI, 2012).Os centros urbanos geralmente apresentam grande riqueza de espécies, que pode ser até maior que os seus entornos(GUO et al, 2018). Esse fato pode estar relacionado com a movimentação de humanos, que pode contribuir com o transporte de propágulos de LUNDHOLM;MARLIN, 2006;KNAPP et al, 2008).…”
unclassified